CULTURAL COSMOLOGIES OF THE INTERNET: SITUATING DIGITAL NETWORKED TECHNOLOGIES IN DIVERSE MORAL UNIVERSES - Maddox, Alexia; Sinanan, Jolynna; Carter , Marcus; Horst, Heather; Spencer, Michaela; Wiesenfeldt, Gerhard (AoIR Selected Papers of Internet Research, 2019)
In this panel we consider how social actors situate uses of technologies within systems of moral norms and values while at the same time compelling the creation of new ones. Popular discourse tends to present dualistic thinking of the positive and negative impacts of technologies. Scholars have engaged with the internet and digital media, emphasising emancipatory subcultures (Coleman 2014; Gehl 2016, 2018) or presenting a critical view of the constraining aspects of networked technologies (Fish & Follis 2019; Fuchs 2014; Lovink 2016). These approaches are complimented by scholarship that considers technological practices and how they are embedded in social and cultural cosmologies (Burrell 2012; Horst & Foster 2018; Miller et. al. 2016). We argue for a closer integration of these bodies of scholarship through an examination of the contentious moral economies operating in emergent social spaces. The panel interrogates the relationship that social, political and economic actors have between their own ideas about what is good, appropriate and right and the diversity of orientations towards trust in techno-bureaucratic systems. We draw attention to immaterial systems and consider the social relationships and individual and collective imaginations that shape the production and experience of networked technologies. Through the papers, we articulate the forms of negotiation, resistance and refusal that occur when diverse moral universes, techno-regulating systems, and the conditions in which people find themselves collide.